The role of reciprocal regulation between TAL1 and miRNA expression in T-cell leukemia progression - Correia, Nádia Grangeon Cavaleiro de Sousa (2014)
Tese de doutoramento, Ciências Biomédicas (Biologia Celular e Molecular), Universidade de Lisboa, Faculdade de Medicina, 2015